Ramping Up Cultural Studies: Pedagogy and the Activation of Knowledge - Offord, Baden (2016)
As a queer person with cerebral palsy (CP), Jacki Brown grew up very aware she was in the minority and this sparked a [passion for social justice issues which she was able to explore when studying cultural studies as part of SCU’s Bachelor of Arts …”I don’t feel like I’m isolated anymore, even with the big challenges in my life. For me, undertaking this degree really has been transformative. I devoted most of cultural studies experience to exploring disability and queer sexuality. It really worked for me and gave me agency in the world.” (Jax Brown, Undergraduate Brochure, Southern Cross University, 2015)